2010
DOI: 10.1002/ejoc.201000867
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Magnetic Properties of a Nitrogen‐Containing Fullerene Dimer

Abstract: We report here on the two‐step synthesis of fullerene dimer 3 from monomer 2. The structures were confirmed by MALDI mass spectrometry, UV/Vis, FTIR, 1H NMR, and 13C NMR spectroscopy. The magnetic properties of the analogous species of dimer 3, N@C140H24O12, were studied by continuous‐wave electron‐spin resonance (CW‐EPR), indicating that the functionalization introduces a permanent zero‐field splitting (ZFS) D = 8.6 MHz and E = 0.45 MHz. The same synthetic procedure could be used to produce a 14N–15N dimer en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
(31 reference statements)
2
8
0
Order By: Relevance
“…In 2011, Porfyrakis et al . also found that there is no change in the hffc and g value for a nitrogen‐containing fullerene dimer, which suggests that the nitrogen atom is still in the center of the cage, confirming the previous report by Dinse . Two years later, the same group reported the synthesis of two dimers 14 N@C 60 ‐C 60 and 15 N@C 60 ‐C 60 .…”
Section: Endohedral Fullerenessupporting
confidence: 80%
“…In 2011, Porfyrakis et al . also found that there is no change in the hffc and g value for a nitrogen‐containing fullerene dimer, which suggests that the nitrogen atom is still in the center of the cage, confirming the previous report by Dinse . Two years later, the same group reported the synthesis of two dimers 14 N@C 60 ‐C 60 and 15 N@C 60 ‐C 60 .…”
Section: Endohedral Fullerenessupporting
confidence: 80%
“…Short reaction times are therefore advantageous because their use may limit the spin loss that has been observed for other dimer reactions involving N@C 60 . 18,19 The reaction scheme, which is based on the Prato method, 22 is shown in Fig. 1.…”
Section: Synthesismentioning
confidence: 99%
“…9,10 Consequently, there are only a small number of examples of N@C 60 derivatization: several monomers, [9][10][11][12][13][14][15] an endohedral fullerene-porphyrin dyad 16 and three types of endohedral fullerene-fullerene dimer. 17,18,19 Recently, we succeeded in synthesizing a covalently linked 14 N@C 60 -14 N@C 60 dimer using highly enriched N@C 60 . 20 However, all of the above involve 14 N@C 60 with 15 N present only in natural abundance.…”
Section: Introductionmentioning
confidence: 99%
“…The products were characterised by a range of analytical tools, and their structures were confirmed by MALDI mass spectrometry, UV-Vis, FT-IR, 1 H NMR, and 13 C NMR spectroscopy. 46 Cyclic nickel and free-base porphyrin dimers including C 70 fullerene both in solution and in crystals were reported. 47 2.1.5 Fullerene derivatives containing halogens.…”
Section: Production Separation and Properties Of Fullerenesmentioning
confidence: 99%